Community Based Stunting Prevention: Learning from Blue Collar Workers’ Children in Indonesia - Muhammad Soffiudin; Winda Putri; Rachel Amanda; Dessy Pratiwi; Firdian Makrufardi (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Background: Stunting remains a major public health challenge in Indonesia, with a 21.5% prevalence in 2023, impacting children’s development and the nation’s human capital. This study aims to provide additional findings on nutritional status of Indonesia under five children in Cianjur and Klaten.Methods: This study conducts a secondary data analysis of survey data among healthy under five children of blue collar workers in 2 areas (Cianjur and Klaten) in Indonesia with a cross-sectional design and combines with existing nutrition status in Indonesia. Various statistical analysis methods were performed accordingly to obtain insights in refining and scaling up stunting prevention strategies. Results: Overall, 236 under five children of blue collar workers were enrolled in this study. We observed that Cianjur has higher under nutritional status overall than Klaten. The Cianjur region have higher underweight status (10.8%), higher stunting status (20.4%), and higher wasting status (4.3%) compared to Klaten (7.7%, 16.8%, and 2.1%, respectively). In comparison with the prevalences of under nutrition coming from latest national survey, Cianjur found to be has lower underweight status (7.0%), lower stunting status (11.4%) and lower wasting status (3.4%) than Klaten (18.6%, 24.5%, and 7.5%, respectively). There is no significant difference stunting proportion between the two areas. Findings from this survey may reflect the impact of initiatives done by local government in reducing the impact of undernutrition (including stunting) among blue collar workers’ children. Conclusion: This study highlights the positive impact of Indonesia’s stunting prevention programs. Further research is needed to strengthen evidence and refine strategies for better child nutrition and health.